2022
DOI: 10.1186/s12877-022-03485-7
|View full text |Cite
|
Sign up to set email alerts
|

Frailty and solid-organ transplant candidates: a scoping review

Abstract: Background There is currently no consensus as to a standardized tool for frailty measurement in any patient population. In the solid-organ transplantation population, routinely identifying and quantifying frailty in potential transplant candidates would support patients and the multidisciplinary team to make well-informed, individualized, management decisions. The aim of this scoping review was to synthesise the literature regarding frailty measurement in solid-organ transplant (SOT) candidates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 137 publications
1
20
0
Order By: Relevance
“…The range of instruments utilised by studies included in this review re ects the lack of consensus regarding the best instruments for assessing frailty(98, 99). This heterogeneity has similarly been reported by scoping reviews examining frailty assessment in acute care settings (25) and solid organ transplantation (100). Assessment settings and contexts were poorly described across studies, although the majority of studies that did provide this detail indicated a propensity for CKD patient assessment in the outpatient setting, while transplant candidates were most commonly assessed at admission for kidney transplantation surgery.…”
Section: Discussionmentioning
confidence: 85%
“…The range of instruments utilised by studies included in this review re ects the lack of consensus regarding the best instruments for assessing frailty(98, 99). This heterogeneity has similarly been reported by scoping reviews examining frailty assessment in acute care settings (25) and solid organ transplantation (100). Assessment settings and contexts were poorly described across studies, although the majority of studies that did provide this detail indicated a propensity for CKD patient assessment in the outpatient setting, while transplant candidates were most commonly assessed at admission for kidney transplantation surgery.…”
Section: Discussionmentioning
confidence: 85%
“…They both contribute to a decline in quality of life because of their contribution to reduced mobility and compromised performance of daily tasks, ultimately leading to a loss of independence. [15][16][17] Frailty significantly increases the risk of mortality while on the waiting list for kidney, lung, liver, and heart transplant. [18][19][20][21] Furthermore, it reduces the likelihood of being listed for kidney transplant by 50% and lowers the probability of receiving a kidney transplant by 32%.…”
Section: Relevance Of Malnutrition Sarcopenia and Frailty On Clinical...mentioning
confidence: 99%
“…30 Finally, frailty has been shown to be associated with higher posttransplant mortality in kidney, 31 lung, 32 heart 33 and liver transplantation. 17 Similarly, sarcopenia has been associated with a 2.0-2.4fold increased risk of mortality while on the waitlist for liver transplant. 34,35 Sarcopenia has also been associated with increased mortality after both living-donor 36,37 and deceaseddonor liver transplant 1 and 3 years 38 posttransplant, as well as after kidney transplant.…”
Section: Relevance Of Malnutrition Sarcopenia and Frailty On Clinical...mentioning
confidence: 99%
See 1 more Smart Citation
“…The FFP is reproducible, clinically coherent with frailty being a wasting disorder with sarcopenia as a key pathophysiological feature, and predicts a wide range of adverse outcomes in the general and solid organ transplantation populations. 14,16 However, it has practical limitations (eg, grip strength and gait speed are not routinely measured in KT candidates, and weight loss poses challenges in the setting of dialysis), 17,18 and the omission of other health domains is not consistent with the solid organ transplantation community's conceptualization of frailty as a multidimensional construct. 18 The Frailty Index (FI) represents the risk state (cumulative deficits) model of frailty.…”
mentioning
confidence: 99%